PENGGUNAAN MEDIA ULAR TANGGA KEBERAGAMAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III SEKOLAH DASAR - Dika Nurunnaja; Ika Ari Pratiwi; Much Arsyad Fardani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The study was conducted to measure the effectiveness of the Snakes and Ladders of Diversity media on the learning outcomes of Pancasila Education of class III of SD 3 Menawan. The study used a quantitative method of the Pre-Experimental model with a One-Group Pretest-Posttest design. Determination of the sample using the saturated sample technique. The sample used all students of class III of SD 3 Menawan with a total of 28 students. Data were obtained through multiple choice written tests and essays on the pretest and posttest. Data analysis used SPSS 26 with the Shapiro-Wilk Technique normality test as a prerequisite test and hypothesis testing with the Paired Sample T-test and N-Gain tests. The normality test showed that the pretest and posttest values ​​were normally distributed. The results of the Paired Sample T-test showed a significant value of 0.00 <0.05, meaning that there was a difference in the pretest and posttest values ​​of the Pancasila Education learning outcomes. The results of the N-Gain test showed that the Pancasila Education learning outcomes increased by 0.6259 with moderate criteria. The results of this study imply that the learning process using game-based learning media such as Snakes and Ladders of Diversity can be a fun and effective learning strategy in improving learning outcomes in Pancasila Education. Teachers are encouraged to utilize similar media to increase active student engagement in learning. Furthermore, schools can further develop other innovative learning media to support more optimal learning outcomes.